Peculiar blood flow profiles among placental chorionic villous vessels of an abnormally thick placenta in a case of systemic lupus erythematosus characterized using microvascular imaging. Issue 12 (12th October 2020) - Inoue, Asami; Horinouchi, Takashi; Yoshizato, Toshiyuki; Kojiro‐Sanada, Sakiko; Kozuma, Yutaka; Ushijima, Kimio
Abstract: We present a patient with systemic lupus erythematosus receiving long‐term steroid therapy, who had myometrial thinning, markedly thickened placenta, and fetal growth restriction (FGR). Blood flow profiles of the myometrium, decidua and placental villous vessels (VV) were described using superb microvascular imaging (SMI) at 35 weeks' gestation. Images showed no decidual blood flow underneath the placenta sitting on a thin myometrium and sparse VV distribution and non‐visualization of peripheral VV flow. Emergency cesarean hysterectomy was performed at 36 weeks. Histological findings showed missing decidua on the thin myometrium, which indicated placenta accreta spectrum, and massive perivillous fibrin deposition and increased numbers of syncytial knots in the placenta. We speculated that the thick placenta and peculiar VV flow profiles resulted from congestion of the intervillous space and intervillous underperfusion/low intraplacental oxygenation, respectively, resulting in FGR. Superb microvascular imaging is useful for diagnosing placenta accreta spectrum and understanding the pathophysiology of thick placenta and FGR.